The Role of Lung Ultrasound in the Management of the Critically Ill Neonate-A Narrative Review and Practical Guide - Lukas Aichhorn; Erik Küng; Lisa Habrina; Tobias Werther; Angelika Berger; Berndt Urlesberger; Bernhard Schwaberger (MDPI AG, 2021)
Lung ultrasound makes use of artifacts generated by the ratio of air and fluid in the lung. Recently, an enormous increase of research regarding lung ultrasound emerged, especially in intensive care units. The use of lung ultrasound on the neonatal intensive care unit enables the clinician to gain knowledge about the respiratory condition of the patients, make quick decisions, and reduces exposure to ionizing radiation. In this narrative review, the possibilities of lung ultrasound for the stabilization and resuscitation of the neonate using the ABCDE algorithm will be discussed.